Ta’tsīru kafā’ati an-naḥwi ‘alā sur‘ati ḥifẓi al-Qur’āni li-ṭalabati Ma‘had Taḥfīẓ al-Qur’ān "Dār as-Salām" Ngelo Gondek Mojowarno. - Muhammad Hapwan Akbari; Fathur Rohman (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2022)
The Qur'an is the holy book of Muslims that Allah revealed to the Prophet Muhammad through the angel Gabriel as a guide to humans and even the whole world. So that the Qur'an is a mercy and guidance for Muslims throughout the ages. Talking about knowing the Qur'an, of course, will not be separated from talking about the language of the Qur'an itself. Since the first time the Qur'an was revealed in Arabic. As for the reason the Qur'an was revealed in Arabic, Arabic at that time had reached qimmah (glory). The Qur'an is mature in terms of qowaid, mufrodat, uslub (language style) and balaghah. In learning Arabic, there are two tools that are very important to learn, namely the science of nahwu and shorof. As a branch of Arabic language science, Arabic grammar. The ability of students in mastering nahwu is usually a separate spotlight for asatidz, musyrif or other fellow students because of their visible advantages in speed of memorizing the Qur'an. The type of research used in this study is a quantitative research method. This study aims to examine whether there is an effect of the level of mastery of nahwu in the speed of memorizing the Qur'an. This research begins by reviewing existing theories and knowledge so that the causes of problems arise. The effect of mastering nahwu on the speed of memorizing the Qur’an for pptq Darussalam students 0.374 can be concluded that there is an influence on the mastery of nahwu with the speed of memorizing the Qur’an.